2020
DOI: 10.3390/nu13010054
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements during COVID-19 Outbreak. Results of Google Trends Analysis Supported by PLifeCOVID-19 Online Studies

Abstract: The use of dietary supplements (DSs) has been steadily increasing all over the world and additionally, the sales of DSs have dynamical increased in the wake of coronavirus disease 2019 (COVID-19) in most of the countries. We investigated DSs phenomenon in 2020 through (1) exploration of Google searches worldwide and in Poland (with Google Trends (GT) tool), and (2) analyses of results of PLifeCOVID-19 Online Studies conducted during the first and second wave of the pandemic. The conducted GT analysis and cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(225 citation statements)
references
References 61 publications
(126 reference statements)
9
157
1
17
Order By: Relevance
“…Since the beginning of the COVID-19 pandemic, the use and sales of dietary supplements have increased globally [ 25 ]. Moreover, the Chinese government has been advising doctors to consider the use of Traditional Chinese medicine for COVID-19 patients in addition to standard care [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, the use and sales of dietary supplements have increased globally [ 25 ]. Moreover, the Chinese government has been advising doctors to consider the use of Traditional Chinese medicine for COVID-19 patients in addition to standard care [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are just some of the many substances and supplements that are currently under investigation but as of yet lack evidence to support their use for the prevention or treatment of COVID-19. While there is plenty of skepticism put forward by physicians and scientists surrounding the use of supplements, these statements have not stopped consumers from purchasing these products, with one study reporting that online searches for dietary supplements in Poland began trending with the start of the pandemic [177]. Additionally, supplement usage increased between the first and second wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These are just some examples of how public health guidance has responded to the emerging evidence regarding vitamin D and COVID-19. Outside of official recommendations, there is also evidence that individuals may be paying increased attention to their vitamin D levels, as a survey of Polish consumers showed that 56% of respondents used vitamin D during the pandemic [177]. However, some companies have used the emerging evidence surrounding vitamin D to sell products that claim to prevent and treat COVID-19, which in one incident required a federal court to intervene and issue an injunction barring the sale of vitamin-D-related products due to the lack of clinical data supporting these claims [178].…”
Section: Vitamin Cmentioning
confidence: 99%
“…These nutraceuticals include "immune boosting" foods and nutrients such as zinc, vitamins, garlic, turmeric, ginger, selenium, etc. (reviewed in [12,13]). In this review, we provide a brief overview of some of the conventional COVID-19 therapies being evaluated, as well as the potential therapeutic properties of nutraceuticals in the treatment and/or prophylaxis of COVID-19.…”
Section: Introductionmentioning
confidence: 99%